An integrated analysis of the relationship between productivity, quality, customer satisfaction, and financial performance in the US airline industry: the application of the resource based view and stakeholder theory - Gebremariam, Belaynesh Teklay (2016)
The relationship between nonfinancial and financial performance measures has been extensively investigated (Banker and Mashruwala, 2007; Banker et al., 2000; Ittner and Larcker, 1998a; Sun and Kim, 2013). However, prior studies have tended to focus their investigation on the relationship between one nonfinancial measure in isolation with another financial measure (Bryant et al., 2004). While these studies provide valuable insights into the contemporaneous and temporal relationship between nonfinancial and financial performance, they are criticized for failing to capture the “trade-off” between various performance measures, which may in turn lead to unreasonable conclusions (Bryant et al., 2004; Ittner and Larcker, 2001). This research, therefore, attempts to address this limitation by conducting a simultaneous investigation of the links between productivity, service quality, customer satisfaction, and financial performance in the US Airline industry. Drawing on the Resource Based View and Stakeholder Theory, an integrative framework is developed to investigate the linkages between airline productivity, service quality, customer satisfaction, and financial performance. This theoretical framework is tested using a longitudinal panel data set drawn from seven major US Airlines over 15 years (1995-2009). Using the partial least square approach to structural equation modelling, findings of this research suggest that improvements in airline productivity can lead to enhancement of service quality as reflected in reductions in flight delays, mishandled baggage, and customer complaints. Airline productivity is also positively linked to current and future periods of financial performance. Further, the results uncovered in this research also suggest that service quality problems, such as flight delays and mishandled baggage, have strong negative effects on current and future customer satisfaction. The results also show that changes in service quality are not reflected concurrently in financial performance. Such changes in service quality are found to have significant impact on future financial performance. However, the link between customer satisfaction and current and future financial performance is not significant. This research contributes to literature by (1) developing an integrative framework drawing on the Resource Based View and The Stakeholder Theory, and (2) identifying the lag length required for the changes on exogenous variables to be reflected on the endogenous variables. Empirically, this research contributes by applying the PLS-SEM that enables simultaneous investigation of multiple variables. It also contributes to practice by providing useful insights for managers for strategy formulation and evaluation.